Molecular Characterization of Some Bacillus Species from Vegetables and Evaluation of Their Antimicrobial and Antibiotic Potency - Moldir Koilybayeva; Zhanserik Shynykul; Gulbaram Ustenova; Symbat Abzaliyeva; Mereke Alimzhanova; Akerke Amirkhanova; Aknur Turgumbayeva; Kamilya Mustafina; Gulnur Yeleken; Karlygash Raganina; Elmira Kapsalyamova (Molecules, 2023)
Numerous natural habitats, such as soil, air, fermented foods, and human stomachs, are home to different Bacillus strains. Some Bacillus strains have a distinctive predominance and are widely recognized among other microbial communities, as a result of their varied habitation and physiologically active metabolites. The present study collected vegetable products (potato, carrot, and tomato) from local markets in Almaty, Kazakhstan. The bacterial isolates were identified using biochemical and phylogenetic analyses after culturing. Our phylogenetic analysis revealed three Gram-positive bacterial isolates BSS11, BSS17, and BSS19 showing 99% nucleotide sequence similarities with Bacillus subtilis O-3, Bacillus subtilis Md1-42, and Bacillus subtilis Khozestan2. The crude extract was prepared from bacterial isolates to assess the antibiotic resistance potency and the antimicrobial potential against various targeted multidrug-resistant strains, including Staphylococcus aureus, Staphylococcus epidermidis, Streptococcus group B, Streptococcus mutans, Candida albicans, Candida krusei, Pseudomonas aeruginosa, Shigella sonnei, Klebsiella pneumoniae, Salmonella enteritidis, Klebsiella aerogenes, Enterococcus hirae, Escherichia coli, Serratia marcescens, and Proteus vulgaris. This study found that the species that were identified have the ability to produce antibiotic chemicals. Additionally, the GC–MS analysis of three bacterial extracts revealed the presence of many antibiotic substances including phenol, benzoic acid, 1,2-benzenedicarboxylic acid and bis(2-methylpropyl), methoxyphenyl-oxime, and benzaldehyde. This work sheds light on the potential of Bacillus to be employed as an antimicrobial agent to target different multidrug-resistant bacterial strains. The results indicate that market vegetables may be a useful source of strains displaying a range of advantageous characteristics that can be used in the creation of biological antibiotics.